Analisis Curah Hujan Terhadap Produksi Padi Sawah di Kecamatan Sipirok Kabupaten Tapanuli Selatan - Imelda Sari Harahap (Journal Agro-Livestock, 2024)
Rainfall is one of the climate elements that directly influences agricultural production, in addition, rainfall is often a limiting factor for agricultural production. The purpose of this study was to analyze rainfall on rice field production in Sipirok District, South Tapanuli Regency. This study uses a survey method. The research data is in the form of secondary data, including rainfall data and rice field production in 2014 - 2023 in Sipirok District, South Tapanuli Regency. Data collection uses documentation techniques. The research data is processed using tabulation and presented in the form of tables and graphs. Data analysis is carried out using Regression and Correlation, then presented descriptively qualitatively and quantitatively. The results of the study indicate that rainfall in Sipirok District, South Tapanuli Regency has a negative effect on lowland rice production where the regression coefficient value is r = 0.4, describing a weak relationship between rainfall variables and lowland rice production, the influence given is 13% while 87% of lowland rice production in Sipirok District, South Tapanuli Regency is influenced by other factors that were not studied.